Budget Participation and Organizational Commitment on Managerial Performance: The Moderating Role of Locus of Control - Nita Kanya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This study analyzes the effect of budget participation and organizational commitment on managerial performance moderated by Locus of control. The population in this study were Regional Apparatus Organisations in West Java Province, totaling 46 OPDs. At the same time, the total sample taken was 92 people responsible for budget preparation and were also involved in budget preparation. The primary data source was obtained by distributing questionnaires to all respondents. The data analysis technique uses multiple regression with the help of the SPSS version 23.00 program. In addition, data quality tests, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test, autocorrelation test), and testing all hypotheses through partial tests, simultaneous tests, and coefficient of determination tests. The results of this study indicate that Budget Participation and organizational commitment have a positive and significant effect on the West Java Provincial Government. Locus of control does not moderate the impact of Budget participation on the performance of the West Java Provincial Government, and LocusLocus of power can negotiate the effect of organizational commitment on the performance of the West Java Provincial Government